Estimation And Design Of Freshwater Fish Pond Using Low Temperature Geothermal Sources At Sungai Klah Hot Springs - Ramly, Farahdyana (Universiti Sains Malaysia, 2017)
Geothermal energy is usually used for electricity uses but low temperature geothermal resources are not suitable for electricity. Hence, low temperature of geothermal resources can be used in agriculture, district heating, and aquaculture. In Malaysia, the uses of low temperature geothermal resources are limited. Mostly, geothermal resources in Malaysia are created as recreation center. Besides being recreation center, the geothermal sources can be used in fish farming or agriculture industries since its cheap and environmental friendly and renewable energy sources. The geothermal sources are able to raise the production and quality of fish because of temperature and chemical content of sources. The temperature and chemical content of geothermal sources is most important and aid production of fish growth. Fish farming or agriculture using low temperature geothermal sources can generate income for entrepreneurs. This research is about estimation and design freshwater fishpond using low temperature geothermal source in Sungai Klah Hot Spring, Perak.